Statistical convergence of order ? in fuzzy normed linear spaces - Cinar, Muhammed; Et, Mikail (Ios Press, 2019)
In this paper, we introduce the concepts of statistically convergent sequences of order beta and statistically Cauchy sequences of order beta in fuzzy normed spaces. Furthermore, we give the relations between statistically convergent sequences of order beta and statistically Cauchy sequences of order beta.
Keywords: Statistical convergence; fuzzy normed linear space; summability